1994
DOI: 10.1038/bjc.1994.198
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the differential expression of marker antigens by normal and malignant endometrial epithelium

Abstract: Summary In order to examine the production of marker proteins, a reproducible method has been established for culturing purified epithelial cells from normal and malignant endometrium. We have examined the differential expression of secretory proteins using immunohistochemistry in frozen tissue sections, immunocytochemistry in cell cultures derived from the same specimens and protein assays on the culture supernatants. Placental al., 1993) and those apparently cured of their endometrial cancer, who yet wis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 20 publications
3
17
0
Order By: Relevance
“…There is speculation that glycodelin may modulate the reaction of the immune system of the patient toward the malignant tumor (28). Both our findings (20) and those of others (14,29) have demonstrated that glycodelin expression is increased in tumor tissues. Glycodelin is expressed mainly in tumor cells and endothelial cells of small blood vessels nearby, which could suggest that the presence of glycodelin might be related to neovascularization in tumor tissues.…”
Section: Discussionsupporting
confidence: 87%
“…There is speculation that glycodelin may modulate the reaction of the immune system of the patient toward the malignant tumor (28). Both our findings (20) and those of others (14,29) have demonstrated that glycodelin expression is increased in tumor tissues. Glycodelin is expressed mainly in tumor cells and endothelial cells of small blood vessels nearby, which could suggest that the presence of glycodelin might be related to neovascularization in tumor tissues.…”
Section: Discussionsupporting
confidence: 87%
“…The basement membrane plays an important part in stromal-epithelial interactions. Whereas glycodelin is a major bioactive protein in the normal secretory endometrium, it has not been detected in endometrial adenocarcinoma tissue (112). But, glycodelin can be induced in endometrial adenocarcinoma cells.…”
Section: Endometrial Cancermentioning
confidence: 95%
“…Patch-clamp recordings were performed on primary cell cultures obtained from endometrial adenocarcinoma samples, essentially according to Chatzaki et al (1994). Briefly, hysterectomy specimens were first trimmed and minced, then dissociated through a first digestion with collagenase II (Roche, 0.05 mg ml Ϫ1 final concentration) at 37˚C for 2 hours, and a second treatment with trypsin/EDTA solution (0.5 g ml Ϫ1 trypsin, 0.2 g ml Ϫ1 tetrasodium EDTA, Sigma) for 10 min at room temperature with constant agitation.…”
Section: Patch-clamp Recordingsmentioning
confidence: 99%